Donde mejor canta un pájaro - Jodorowsky, Alejandro (Libros del tiempo (Madrid, Spain), 2015)
"Alejandro Jodorowsky tells the story of how his Ukrainian Jewish grandfather, his fiery wife, Teresa, and their four children moved to Chile under fake passports and assumed Christian identities, with only a half-kopek to their name and no idea how they'd forge their new lives. His book is a family saga filled with ancestors both mythical and real including bee-covered relatives, women who commune with wolves, snake charmers, and militant anarchists"--